The advisory opinion mechanism before the European court of human rights: prelude to establishing a delicate balance in the relationship between French and European judges - Danelciuc-Colodrovschi, Nataşa (Journal of the Belarusian State University. Law, 2020)
Protocol No. 16 to the European Convention on the Protection of Human Rights and Fundamental Freedoms – entered into force on 1 August 2018 after its ratification by France – extended Strasbourg Court’s competence to give advisory opinions at the request of the highest courts or tribunal of contracting parties. This new mechanism aims to enhance the interaction between European judges and national authorities and reinforce implementation of the convention in accordance with the principle of subsidiarity. Nevertheless, the new procedure seems to have been conceived under a contradiction. Its analysis, as well as that of the first advisory opinion given at the request of the French Court of Cassation, raises a certain number of questions regarding the real respect of the margin of appreciation that remains to the member states in the context of a possible emergence of a «controlled» subsidiarity.